(untitled) (FUDMA JOURNAL OF SCIENCES, 2022)
Spinal cord injury (SCI) may occur as a result of traumatic crash to the spine that dislocates one or many vertebrae. SCI has two events to bring about the injury in the spinal cord that result at the end it will lead to bad consequences and loss of neurons; SCI complications are general loss of motor and sensory function. Extracellular vesicles (EVs) are very small vesicles produced by cells that contribute to cell to cell communication, transferring bioactive lipids, proteins, RNA. The aim of this research is to determine the effect of EVs on inflammasomes complex after SCI on rats. EVs were harvested characterized and cultured as exosomes, the animals are divided to 5 groups: control, sham, vehicle, SCI + treatment, SCI + EVs group. Spinal cord injury was induced using weight compression. 10 Î¼l of EVs were injected intrathecally into lumber cistern in a space between L4-L5 laminae slowly. Gene expression of Caspase-1, ASC and NLRP3 were determined by RT-PCR. Western blot for determining the protein content of the inflammasomes were carried out. SCI up regulated the level of inflammasome complex both mRNA and proteins. Inthrathecal injection of EVs down regulated the inflammasome complex and make neuronal recovery. SCI can up regulate the level of inflammasome complex both mRNA and proteins. EVs are good therapeutic agent for SCI and increase neuronal recovery, inthrathecal injection is the best method of injection MSCs for treatment of SCI.